Global Diffusion and Adoption of Technologies for Knowledge and Information Sharing
DOI: 10.4018/978-1-4666-2142-8.ch004
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Factors, Knowledge Processes and Performance in Global Sourcing of IT Services

Abstract: In this paper, the authors explore the influences of two major contextual factors—supplier team members’ cultural understanding and trust relationship—on knowledge processes and performance in global sourcing of IT services. The authors discuss a joint investigation conducted by a cross-cultural research team in China. Cultural understanding is measured by individualism with guanxi and mianzi, two Chinese cultural concepts, and trust relationship is measured by adjusting trust, a notion reflecting the uniquene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…One more possible limitation of our study could be related to the fact that we did not specifically examine the role of the type of business that the born‐global firm is engaged in on their IT capability. It is likely that an IT outsourcing supplier might have greater IT capability compared with an export‐oriented manufacturer (Du et al. , 2011a).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…One more possible limitation of our study could be related to the fact that we did not specifically examine the role of the type of business that the born‐global firm is engaged in on their IT capability. It is likely that an IT outsourcing supplier might have greater IT capability compared with an export‐oriented manufacturer (Du et al. , 2011a).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…In contrast, knowledge sharing is not a significant element in relationship dimension. According to Du et al (2011), knowledge sharing is a complex and incremental phenomenon, which should be related to social aspects such as culture and trust. In the cultural theory of "Collectivism", "Guanxi" is defined as a series of activities carried out by the parties concerned within their network and that it is all about the cultivation of long-term personal relationships (Ramasamy et al, 2006).…”
Section: Common Methods Biasmentioning
confidence: 99%
“…Another explanation might be that the impact of knowledge sharing on performance is not an immediate one and it may have delayed effects (Du et al, 2011).…”
Section: Common Methods Biasmentioning
confidence: 99%
“…A wealth of studies on ISD outsourcing has observed the relationship between the client and the outsourcing partner (Du et al, 2011;Alami et al, 2008;Fisher et al, 2008). These studies have mainly observed:…”
Section: Introductionmentioning
confidence: 99%